Downregulated expression of S2-RNase attenuates self-incompatibility in "Guiyou No. 1" pummelo. (1st September 2021) - Hu, Jianbing; Xu, Qiang; Liu, Chenchen; Liu, Binghao; Deng, Chongling; Chen, Chuanwu; Wei, Zhuangmin; Ahmad, Muhammad Husnain; Peng, Kang; Wen, Hao; Chen, Xiangling; Chen, Peng; et al.
Abstract: Self-incompatibility (SI) substantially restricts the yield and quality of citrus. Therefore, breeding and analyzing self-compatible germplasm is of great theoretical and practical significance for citrus. Here, we focus on the mechanism of a self-compatibility mutation in 'Guiyou No. 1' pummelo ( Citrus maxima ), which is a spontaneous mutant of 'Shatian' pummelo ( Citrus maxima, self-incompatibility). The rate of fruit set and the growth of pollen tubes in the pistil confirmed that a spontaneous mutation in the pistil is responsible for the self-compatibility of 'Guiyou No. 1'. Segregation ratios of the S genotype in F1 progeny, expression analysis, and western blotting validated that the reduced levels of S 2 - RNase mRNA contribute to the loss of SI in 'Guiyou No. 1'. Furthermore, we report a phased assembly of the 'Guiyou No. 1' pummelo genome and obtained two complete and well-annotated S haplotypes. Coupled with an analysis of SV variations, methylation levels, and gene expression, we identified a candidate gene ( CgHB40 ), that may influence the regulation of the S 2 - RNase promoter. Our data provide evidence that a mutation that affects the pistil led to the loss of SI in 'Guiyou No. 1' by influencing a poorly understood mechanism that affects transcriptional regulation. This work significantly advances our understanding of the genetic basis of the SI system in citrus and provides information on the regulation of S-RNase genes.